'Finding the image': using photos to give voice to teacher educator professional learning. Issue 2 (3rd May 2020) - Parker, Melissa; Ní Chróinín, Déirdre; Coulter, Maura; McFlynn, Paul; Walsh, Ciaran
ABSTRACT: Our purpose was to explore the role of photocue reflection in the professional learning of physical education teacher educators. Five physical education teacher educators participated in a six-month professional learning experience focused on communication. Individual diaries including both photos and writing prompts, photocue reflective diaries, were used as both a learning tool and data source within a self-study of teacher education practices methodological frame. Two themes represented the use of photocue reflection: the multidimensional nature of the professional development experience and the use of photocue reflection to enhance reflective processes by supporting reflection on reflection-in-action. Photocue reflection supported identification and analysis of meaningful events related to communication. The processes helped participants to appreciate the significance of communication, clarifying understandings, and making connections to their teacher education practices. Insight is shared on the merits of photocue reflection in scaffolding professional learning experiences and in combining both a learner and teacher role within professional development activities.